MULTI-STAGE ORIGIN OF THE LOWER CRUST OF THE KARELIAN CRATON FROM 3.5 TO 1.7 GA BASED ON ISOTOPIC AGES OF KIMBERLITE-DERIVED MAFIC GRANULITE XENOLITHS - Peltonen P.; Mänttäri I.; Huhma H.; Whitehouse M.J. (My University, 2006)
Mafic garnet granulite xenoliths recovered from ∼500 to 600 Ma old eastern Finland kimberlites provide direct information on the petrology and physical properties of the lower cust below the Archean Karelian craton. Mineral thermobarometry, together with isotopic, petrological and seismic velocity constraints, imply that the xenolith suite is derived from a geophysically-determined, dense, high-velocity layer at the base of the crust (40–58 km depth). Single grain zircon U–Pb dates and Nd model ages (TDM) imply that this is a hybrid layer consisting of both Archean and Proterozoic mafic granulites. Zircon ages of up to ∼3.5 Ga and Nd TDM model ages ∼3.7 Ga of the xenoliths are equivalent to those of the oldest upper crustal assemblages. During the Proterozoic, transient heating of these Archean granulites by voluminous basic magmatic intrusions resulted in multiple younger zircon generations within individual xenoliths. The most important post-Archean lower crust growth took place during ∼1.9 Ga accretion of the Svecofennian arc complex to the craton margin, when underplating Proterozoic basaltic magmas became mingled with pre-existing Archean mafic granulites. Later, post-orogenic (∼1.80–1.73 Ga) transient heating of the lower crust occurred as a response to magmas ponded at the uppermost lithospheric mantle. In conclusion, Karelian lower crust records the geological evolution of the craton margin environment through a period of nearly 4 billion years. Our data add a new piece to the emerging picture that emphasises the global importance of the 3.5 Ga crustal growth
Keywords: Precambrian::Archean::Paleoarchean; Докембрий::Архей::Палеоархейская